2012
DOI: 10.1371/journal.pone.0029668
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of the Influence of Valence and Arousal on the Implicit Processing of Affective Pictures

Abstract: In the current study, we investigated the time course of the implicit processing of affective pictures with an orthogonal design of valence (negative vs. positive) by arousal (low vs. high). Previous studies with explicit tasks suggested that valence mainly modulates early event-related potential (ERP) components, whereas arousal mainly modulates late components. However, in this study with an implicit task, we observed significant interactions between valence and arousal at both early and late stages over bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
39
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 82 publications
10
39
1
Order By: Relevance
“…Intriguingly, in this latter study, the occipital negativity associated with the detection of task-relevant stimulus features was accompanied by a frontal positivity, which is highly consistent with the pattern in the present study. The frontal and parietal modulations in the N200 and P300 time range, respectively, are furthermore in line with studies in which participants encountered affective stimulus material [e.g., [31], [33], [34], [35]] and in reward paradigms investigating ERP responses to reward-predicting cues, as well as to rewarded target stimuli [16], [18][20]. Moreover, similar modulations in the N200/P300 range are commonly observed in studies focusing on reward feedback [e.g., [17], [36]].…”
Section: Discussionsupporting
confidence: 86%
“…Intriguingly, in this latter study, the occipital negativity associated with the detection of task-relevant stimulus features was accompanied by a frontal positivity, which is highly consistent with the pattern in the present study. The frontal and parietal modulations in the N200 and P300 time range, respectively, are furthermore in line with studies in which participants encountered affective stimulus material [e.g., [31], [33], [34], [35]] and in reward paradigms investigating ERP responses to reward-predicting cues, as well as to rewarded target stimuli [16], [18][20]. Moreover, similar modulations in the N200/P300 range are commonly observed in studies focusing on reward feedback [e.g., [17], [36]].…”
Section: Discussionsupporting
confidence: 86%
“…Focused on emotional arousal, some studies have demonstrated that highly emotionally arousing stimuli elicit more pronounced P300 waves than low emotionally arousing stimuli, even when these stimuli are presented without awareness (Feng, Wang, Liu, Zhu, Dai, Mai, & Luo, 2012;Rozenkrants, Olofsson, & Polich, 2008). These previous findings are in accord with the current study, confirming that emotional arousal increases P300 responses to probes in the CIT, regardless of conscious awareness.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it remains unclear whether crime-related stimuli are also automatically recognized in the CIT, like selfname stimuli. Previous studies have demonstrated that highly emotionally arousing stimuli elicit more pronounced P300 waves than less emotionally arousing stimuli, even when these stimuli are presented without conscious recognition (Feng, Wang, Liu, Zhu, Dai, Mai, & Luo, 2012;Rozenkrants, Olofsson, & Polich, 2008). In line with these studies, a crime-related probe might also be processed via the bottom-up route if it is perceived unconsciously.…”
Section: Introductionsupporting
confidence: 61%
“…Our result is consistent with their finding of P2, which was elicited differently by beautiful and less beautiful pendants. Many previous ERP studies have provided evidence that emotional content in pictures (if it existed) was still evaluated even in an implicit nonemotional task and different emotions were reflected in the difference in P2 amplitude [16,17,23]. These findings supported the point that early emotional evaluation is an automatic process [24].…”
Section: Discussionmentioning
confidence: 52%